REFLECTIONS OF MYTHOLOGICAL BIRDS IN VISUAL SENSE TO THE PRESENT - Akbulut, Nevin (TÜRKİYE TEMEL BİLİMLER ARAŞTIRMA VAKFI, 2021)
Since the earliest civilizations, all people have always wondered about the beginning of the universe they live in and the mystery about whether there are places to live outside of the world. Thoughts and interpretations arising from this sense of curiosity laid the founda tions of mythology. Since mythology is the reflection of the traces of the past to the present, it is accepted as the first reference source of the national and cultural lives of the nations. The most striking concept among the concepts wondered in mythology was the concept of "sky" and its elements. Covering the universe, being infinite and inaccessible; The sky has a special importance in mythology since the existence of human beings, as it is a shelter for many amazing beings such as God, sun, moon and star. The beings that can fly in the sky, which are seen as a personal God who directs the life of man, have also been accepted as sacred by all societies and have shown their existence in almost many cultural elements. Since the act of “flying” is an act that human beings cannot do but admires, all beings who can do this act are seen close to God and blessed. When it comes to the act of flying, the first thing that comes to mind is birds. In addition to being seen as the ruler of the sky, birds have taken their place in many cultures, sometimes with extraordinary qualities, and sometimes as a symbol of sovereignty, beauty, state, power, and luck, as living things that continue their influence from the past to the present. In this article, by considering the value of the sky in mythology, after examining the place of a few of the birds (phoenix, hüma, eagle, crane, falcon, sungur, tulpar) as mythological flying creatures belonging to the sky in Turkish culture and mythology, it has been tried to determine that these beings' reflections and symbolic effects continue to the present day. It has been revealed that although mythological elements are associated with the past, they still maintain their visual and symbolic effect.

En eski uygarlıklardan itibaren bütün insanlar, yaşadıkları evrenin başlangıcını ve dünya dışında yaşanabilecek yerlerin olup olmadığı ile ilgili gizemi hep merak etmişlerdir. Bu merak duygusundan doğan düşünce ve yorumlar, mitolojinin temelini atmıştır. Mitoloji, geçmişin izlerinin günümüze yansıması olduğu için milletlerin millî ve kültürel hayatlarının ilk başvuru kaynağı olarak kabul görmektedir. Mitolojide merak edilen kavramlar arasında en dikkati çeken “gök” kavramı ve ona ait unsurlar olmuştur. Evreni kaplaması, sonsuz ve ulaşılmaz oluşu; Tanrı, Güneş, Ay ve yıldız gibi birçok hayranlık uyandıran varlığa barınak olması sebebiyle insanın var oluşundan itibaren gökyüzü mitoloji içerisinde ayrı öneme sahiptir. İnsanın hayatını yöneten, kişisel bir Tanrı olarak görülen gökyüzünde uçabilen varlıklar da tüm toplumlar tarafından kutsal kabul edilmiş, hemen hemen birçok kültürel öge içerisinde varlığını göstermiştir. “Uçmak” eylemi insanoğlunun yapamadığı bununla birlikte hayranlık duyduğu bir eylem olduğundan bu eylemi yapabilen tüm varlıklar da Tanrı ile yakın görülmüş ve kutsanmıştır. Uçmak eylemi denilince akla gelen ilk unsur, kuşlar olmuştur. Kuşlar, gökyüzünün hâkimi görülmesinin yanı sıra, birçok kültür içerisinde bazen olağanüstü vasıflar yüklenerek bazen de hükümdarlık alameti, güzellik, devlet, güç, baht sembolü olarak geçmişten günümüze etkisini sürdüren canlılar şeklinde yerini almıştır. Bu yazıda mitoloji içerisinde gökyüzünün taşıdığı değer ele alınarak göğe ait mitolojik uçabilen varlıklar olarak kuşlardan birkaçının (anka, hüma, kartal, turna, doğan, sungur, tulpar) Türk kültüründe ve mitolojisinde yeri incelendikten sonra bu varlıkların günümüze yansımaları ve simgesel anlamda etkilerinin sürdüğü tespit edilmeye çalışılmıştır. Mitolojik unsurların her ne kadar geçmiş ile bağdaştırılsa da görsel ve simgesel anlamda etkisini hâlen devam ettirdiği ortaya konulmuştur.
MİTOLOJİK KUŞLARIN GÖRSEL ANLAMDA GÜNÜMÜZE YANSIMALARI
Keywords: Creative Arts and Writing; Sanat ve Edebiyat